CROSS-CULTURAL COMMUNICATION IN ACADEMIC COLLABORATION: A BELF PRESPECTIVE ON INDONESIAN-DUTCH HIGHER EDUCATION PARTNERSHIP DURING WINNER 2024 - Pramesti, Intan; Rezki Fatimah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines cross-cultural communication strategies between Indonesian and Dutch partners during the WINNER 2024 conference, with a focus on the use of Business English as a Lingua Franca (BELF). The study aims to identify the pragmatic communication strategies used by Indonesian and Dutch participants, analyzing the interaction, cultural expectations challenge, and uncover the challenges faced during the collaboration. Using a qualitative case study method, this research analyze three selected sessions from WINNER 2024 that publicly available on youtube channel, applying BELF strategies, and combining cultural awareness framework between Hofstede's power distance theory, Hall's high/low context theory, and Ting-Toomey's face negotiation theory. The findings show that both Indonesian and Dutch participants adapted their use of English through simplification, repetition, and clarification to ensure mutual understanding. Cultural dynamics found in this interaction is: Indonesians preferred high-context and hierarchical expressions, while Dutch speakers preferred low-context and egalitarian communication. Face-saving strategies and power distance also shows conversational patterns. This study conclude that the combination of communication flexibility and cultural awareness make effective collaboration and minimize cultural communication gaps. This research contributes to applied linguistics studies by demonstrating how BELF used in real-time academic collaboration.